PENGARUH KEPEMIMPINAN DALAM MENINGKATKAN KINERJA ANGGOTA DPRD DI KOMISI B KABUPATEN KUTAI TIMUR - Ati, Sumi (PREDIKSI, 2016)
ABSTRACTSUMIYATI.Influence Leadership in Improving Public Service Commission B DPRD members of the East Kutai Regency under the guidance of Mrs. Dra.Hj.Nanik Pujiastuti, M.Si as Supervisor I and Mr. Suhardiman, S. Sos, M.Si as Supervisor II.The purpose of this study is to get an objective answer to solve the problems that are formulated so that it can be used to test the hypothesis that the writer suggested.To find out more about Influence Leadership in Improving Public Service Commission B DPRD members in East Kutai in this function as a variable causes.To improve good public service, then the leadership must be concerned about the coordination, motivation and control so that the members of Commission B in their job as best as possible, so that the public service employees of Commission B DPRD member of East Kutai Regency can be improved.This is evident from the results of analysis of leadership variable has a very strong relationship with the public service variables of Commission B DPRD members in East Kutai, this can be seen from the results of product moment correlation coefficient, where r s = 0.968.Based on the results of the analysis, it is clear that the hit r = 0.968> r tab = 0482 at a significance level of = 0.05.Based on the results of the calculation of the overall correlation coefficient r s = 0.968 for n = 17 is distributed into the formula then gained 0.443 hypothesis is greater than the value t table of 1.753 for n - 2 = 15 at significance level of 0.05.